Fatigue Life Amphibious Floater based on RAO Slamming Pressure - Priohutomo, Kusnindar; Nugroho , Wibowo Harso; Arianti, Erdina; Hidayat, Dony; Pinindriya, Sinung Tirtha; Yulfani, Rosi Dwi; Sugiarto, Muria Armansyah; Ismail, Muhammad Fajariansyah; Eritha, Fadila Norasarin; Choiriyah, Isma (International Journal of Marine Engineering Innovation and Research, 2026)
Floater is one of the most important part of amphibious version plane and conducting study of it becomes one of the featured research to support Indonesia’s transportation. This paper examined general study of amphibious floater slamming load when landing on the water in the various plane landing situation, starting from stern 5°, stern 10°, bow 5°, bow 10°, heel 0°, heel 5° and heel 10°. Carbon Fiber Reinforced Polymer (CFRP) material is used with 20 and 40 mm thickness. Floater consists of three main parts which are base, keel, and frame. Seaplane is designed to withstand 1000 cycle (500 landing and 500 take off cycle) in a year. This paper confirms that with the thickness of 20 and 40 mm, and heel position of 0°, floater can withstand up to 65,535 years. In contrary, using the 20 and 40 mm layer when landing with any combination position, the floater can’t last and only has 0.01 year of fatigue life.